STUDI KELAYAKAN MEDIA EDUKASI CARIES CASTLE BOX DI LINGKUNGAN GURU TK - Maulida, Nadilla Nurul; Ningrum, Nining; Putri, Megananda Hiranya; Widyastuti, Tri (Poltekkes Kemenkes Bandung, 2025)
The use of interesting educational media will facilitate student understanding and motivate student to improve learning effectiveness. Caries Castle Box is used as an educational media for the introduction of dental caries combined with games. The purpose of this study was to determine the feasibility of Caries Castle Box educational media from the perspective of kindergarten teachers and entrepreneurship. This type of research was descriptive with a qualitative approach with a research design using feasibility study approach. Taking test subjects using non probability sampling, precisely purposive sampling, which is based on researcher considerations. The test subject included 2 material experts, 2 media experts, entrepreneurship expert and user responses, that are 3 kindergarten teachers. The assessment conducted by experts assessed that this media is feasible to be tested, the assessement of the user response, that are 3 kindergarten teachers, assessed that this educational media is considered effective and feasible to use for early childhood. The results of this study indicate that the Caries Castle Box educational media is feasible in terms of entrepreneurial aspects and is declared very feasible to be used as educational media for early childhood to recognize the world of dental health, especially dental caries.